A novel AES–DES with improved Cheetah optimisation algorithm for secured medical data transmission in cloud environment - Joel, Gunde; Manikanta Kasyap, Chaturvedula V. Narasimha; Sidiq, Shaik Abubakar; Riyaz, Jammimanu; Santhi Sri, T.; Sreedevi, Pogula (Journal of medical engineering & technology, 2024)
In recent years, transmitting medical data has been a regular process. Although strong, safe, and dependable encryption techniques are necessary for medical data, cryptography is largely a computational process. The research presents a selective encryption approach for the transfer of sensitive data. This study proposes a novel technique for selecting the optimal keys to offer more security to medical data. Initially, the medical data is encrypted using the hybrid AES-DES technique. To make an efficient encryption method, the most optimal keys are selected utilising an improved Cheetah optimisation algorithm (ICO). Finally, the keys are optimised, and the input medical data is safely kept in the cloud system according to the established model. As a result, the proposed approach utilises the Python tool to evaluate the results. The simulation results show that the proposed method outperforms others in terms of encryption time 96 s, decryption time 92 s, memory usage (16), and latency (0.006).